Trust-based security for Ad-Hoc network (International Journal of Engineering and Computer Science, 2017)
A mobile Ad-hoc network (MANET) is decentralized type, infrastructure less wireless network of mobile nodes. Since the nodes are mobile, the network topology may change rapidly and unpredictably over time. The network is decentralized, where all network activity including discovering the topology and delivering messages must be executed by the nodes themselves. i.e., routing functionality will be incorporated into mobile nodes. Due to multi-hop routing and absence of centralized administration in open environment, MANETs are vulnerable to attacks by malicious nodes. In order to decrease the hazards from malicious nodes, a simple trust model is built to evaluate neighbors’ behaviors using forwarding packets. Extended from the Ad-hoc on demand distance vector (AODV) routing protocol , a trust-based reactive multipath routing protocol, Ad-hoc on-demand trusted-path distance vector (AOTDV), is proposed for MANETs. This protocol is able to discover multiple loop-free paths as candidates in one route discovery. These paths are evaluated by two aspects: hop counts and trust values. From these paths shortest path is chosen that meet the requirements of data packets for dependability or trust. Several experiments have been conducted to compare AODV and AOTDV protocols and the results show that AOTDV improves packet delivery ratio and reduce the impairment from black hole.